Gold recovery from dilute aqueous solution by a biosorbent derived from woody biomass. Issue 12 (1st November 2021) - Pan, Hsiang-Wei; Iizuka, Atsushi; Shibata, Etsuro
Abstract: A low-cost and eco-friendly sorbent, a woody biomass derived sorbent (biosorbent), has been prepared by chemical modification of wood. To improve the Au(III) sorption performance and economic feasibility for Au recovery from dilute aqueous solution, the preparation process has been optimized by changing the preparation conditions. The Au(III) sorption performance and characterization by Fourier transform infrared spectroscopy and scanning electron microscopy show that sulfuric acid treatment increases the number of active sites and porous structure on the woody biosorbent surface. The woody biosorbent shows considerable Au sorption ability even for very low Au concentration (initial [Au(III)] ≥ 0.025 mmol/L was tested in the present study). Furthermore, visible elemental gold particles form, indicating that Au(III) is subsequently reduced to metallic gold by the redox reaction on the sorbent surface. The adsorption–reduction mechanism is explained for the complete Au(III) sorption process by the results of a kinetic study, the sorption isotherm, and the gold reduction phenomenon. The sorbent is highly selective for Au(III) over other base metals and can recover Au(III) from waste water containing high levels of impurities. Considering its remarkable Au(III) uptake performance, selectivity in dilute solution, and extremely low cost and simple production, the woody biosorbent is a promising candidate for gold recovery from dilute aqueous solution.